2022
DOI: 10.5829/ije.2022.35.10a.11
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Onboard Wi-Fi Module Antennas in Terms of Orientation and Position for IoT Applications

Abstract: With ever increasing demand of IoT based sensor systems, there is a need to assess the performance of wireless sensor networks especially in indoor environment. In these networks, antenna plays an important role. The performance of onboard antenna of the sensor module with respect to its height and orientation are examined in this paper. Several experiments were carried out mostly in indoor environment by changing orientation and height of the antennas. The performance is assessed on the basis of Received Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These distributed points are called scatter plot, which is used to characterize accuracy of IRNSS receiver. The area within which the estimated parameters are likely to be is the confidence region [9,10,19]. The performance of IRNSS is statistically quantified by analyzing the confidence region.…”
Section: Accuracy Measures In 2dmentioning
confidence: 99%
See 1 more Smart Citation
“…These distributed points are called scatter plot, which is used to characterize accuracy of IRNSS receiver. The area within which the estimated parameters are likely to be is the confidence region [9,10,19]. The performance of IRNSS is statistically quantified by analyzing the confidence region.…”
Section: Accuracy Measures In 2dmentioning
confidence: 99%
“…When both the receivers are nearby (within the vicinity of the reference station), they are affected by the errors which are common to both the receivers. These common errors can be eliminated completely or reduced by transmitting the differential corrections from the reference station to the rover receiver [8][9][10]. The ephemeris error and satellite clock error can be eliminated completely.…”
Section: Introductionmentioning
confidence: 99%
“…One of the 5G plans is to employ the sub-6 GHz band -n34(2010-2025 MHz), n38 (2570-2620 MHz), n40 (2300-2400 MHz), n41 (2496-2690 MHz), n46 (5150-5925 MHz), n77 (3300-4200 MHz), n79 (4400-5000 MHz), etc.which, also covered mid-band of 5G (2 to 6 GHz), leading high data rates, huge capacity as well as good coverage from the essential number of available spectrums [3,4]. Modern wireless communications stretch out to new standard applications, algorithms, propagation techniques [5,6], vigorous hardware defiance as well as the relevant antenna design [7][8][9][10] fulfilling human needs. As the performance of the antenna results considerable influence on the accomplishment of the plenary communication systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, very little research on Galileo's performance evaluation over India has been reported [9]. There are also some studies mainly focusing on the accuracy of navigation systems related to multiple GNSS components [10][11][12][13]. In this research work, an attempt has been made to enhance position accuracy using integrated ground-and space-based observations.…”
Section: Introductionmentioning
confidence: 99%